(3eaGgje hJWHjbGJs - (3HTjQ(B, (3GdYdGbs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2008)
(3jJfGhd gPG GdcJGH GdaUhd GdJGdjI (B: (3eONd Gdi GdJNWjW GdJShjbj (B-(3GdJMdjd GdNGQLj (B-(3GdJMGjG GdOGNdj (B-(3JMdjd ecGef GdbhI hGdVYa hGdaQU hGdJgOjOGJ (B-(3GSJQGJjLjI GdefJL (B-(3GdJfHD HGdHjYGJ hGdGSJQGJjLjI (B-(3JfajP GdGSJQGJjLjI (B-(3GdGJUGdGJ hOhQgG aj JfajP GdGSJQGJjLjI (B-(3HMhK GdJShjb (B-(3GdJfajP hGdQbGHI (B-(3cJGHI GdNWI(B.s
(3HjHdjhZQGajG (B283(3U(B.s
Keywords: (3GSJQGJLjI GdJShjb , GdJNWjWs; (3GdJShjbs; (3HMhK GdJShjbs